TPACK in Early Childhood Education: A Bibliometric Analysis of Global Research (2017–2025) - Maisarah Maisarah; Cyndi Prasetya; Nova Yurika (Jurnal Raudhah, 2025)
Research on Technological Pedagogical Content Knowledge (TPACK) in early childhood education has grown rapidly along with the increasing integration of technology in learning. However, comprehensive mapping of research trends and themes remains limited. This study aims to conduct a bibliometric analysis of scholarly publications on TPACK in early childhood education. This quantitative study employed a bibliometric approach. The population consisted of all TPACK-related early childhood education articles indexed in Scopus and Google Scholar, with a sample of 312 articles published between 2017 and 2025. Data were collected using documentation sheets and analyzed with VOSviewer software. Bibliometric descriptive analysis and visualization of keyword, author, and citation networks were applied. The findings reveal a significant increase in TPACK-related publications, with dominant themes focusing on teacher competence, digital technology integration, and play-based learning in early childhood settings.